2014
DOI: 10.1016/j.pbb.2014.03.024
|View full text |Cite
|
Sign up to set email alerts
|

5-HT1A receptor activation reduces fear-related behavior following social defeat in Syrian hamsters

Abstract: Social defeat leads to selective avoidance of familiar opponents as well as general avoidance of novel, non-threatening intruders. Avoidance of familiar opponents represents a fear-related memory whereas generalized social avoidance indicates anxiety-like behavior. We have previously shown that serotonin signaling alters responses to social defeat in Syrian hamsters, although it is unclear whether serotonin modulates defeat-induced fear, anxiety, or both. In this study we focus on 5-HT1A receptors, in part, be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 59 publications
(67 reference statements)
3
15
0
Order By: Relevance
“…Activity-regulated cytoskeletal-associated protein (Arc) is an immediate early gene and a commonly used marker of synaptic plasticity, as it is necessary for the consolidation of long-term memory (Ploski et al, 2008). Recently, we showed that social defeat increases the expression of Arc in the BLA of Syrian hamsters (Bader et al, 2014), which is consistent with other research showing that Arc in the lateral amygdala is necessary for the reconsolidation of auditory fear conditioning (Maddox & Schafe, 2011). Taken together, these findings suggest that the acquisition of conditioned fear and CD is regulated by a similar set of cellular and molecular mechanisms in the BLA.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Activity-regulated cytoskeletal-associated protein (Arc) is an immediate early gene and a commonly used marker of synaptic plasticity, as it is necessary for the consolidation of long-term memory (Ploski et al, 2008). Recently, we showed that social defeat increases the expression of Arc in the BLA of Syrian hamsters (Bader et al, 2014), which is consistent with other research showing that Arc in the lateral amygdala is necessary for the reconsolidation of auditory fear conditioning (Maddox & Schafe, 2011). Taken together, these findings suggest that the acquisition of conditioned fear and CD is regulated by a similar set of cellular and molecular mechanisms in the BLA.…”
Section: Introductionsupporting
confidence: 91%
“…On the other hand, social defeat has been shown to increase anxiety-like behavior in an open field test as indexed by reduced locomotion and reduced time spent in the center of the arena (Raab et al, 1986, Meerlo et al, 1996, Kinsey et al, 2007). Also, Syrian hamsters generalize social avoidance to novel intruders suggesting that conditioned defeat involves an increase in anxiety-like behavior (Bader et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…In the social interaction test, one restrained animal briefly showed submissive behavior toward the intruder, and several restrained animals displayed aggressive behavior. These data are similar to agonistic behavior displayed by non-stressed hamsters in a resident-intruder paradigm, and indicate that acute restraint stress does not alter subsequent agonistic behavior [16, 19, 34, 37]. In the other behavioral tests, restrained animals tended to differ from non-restrained controls on some measures, but not always in a direction that would be considered anxiety-like.…”
Section: Resultssupporting
confidence: 67%
“…In the learned helplessness model, uncontrollable tail shock sensitizes the caudal DRN, and serotonergic projections from the caudal DRN to the DS and BLA mediate escape deficits and anxiety-like behavior, respectively [6568]. In the conditioned defeat model, acute social defeat activates the rostral DRN and serotonergic projects to the BLA modulate the changes in agonistic behavior characteristic of the conditioned defeat response [16, 34, 63, 69]. Interestingly, subordinate social status appears to sensitize several DRN subregions such that subsequent social defeat stress leads to elevated neural activity in the rvDRN whereas subsequent restraint stress increases neural activity in the cdDRN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation